The New Mars Synthesis : Circumstantial Evidence of a Past Persistent Gaia on the Red Planet (Global Journal of Science Frontier Research, 2023)
Based on a large scale synthesis of data, Mars can be understood to be a planet with a flourishing, Gaia-type, biosphere in the past, where life modified its environment from an early epoch so that it became the home of a massive Earth-like biosphere, before an anomalous mass extinction event, reduced it to its present state with only a weak, residual biosphere. Such a possibility is strongly suggested by circumstantial evidence gathered form a variety of sources. The Mars crate ring rate, is shown to be much higher than Lunar leading to the average surface age in the Northern Hemisphere to be approximately 1/2 billion years or less. This is proven by the average age of younger Mars meteorites, the Nakhlites and Shergottites, of less than 1 Billion years. The young surface ages make signs of liquid water on Mars more recent and indicate that the liquid water epoch on Mars lasted for most of Mars geologic history. This requires a high pressure CO 2 greenhouse in the presence of large amounts of ferrous silicates, requiring, in turn, a high oxygen level atmosphere to provide geochemical stability. This results in a red Mars due to large amounts of Hematite in the soil and few carbonates. This oxygenated atmosphere, in turn, requires massive photosynthesis, as occurs on Earth, since UV photolysis of water is self-limiting whereas photosynthesis is self-amplifying by formation of an ozone layer to protect plant life. Mars thus became very Earthlike in environment, with a mixed CO 2 and CH 4 greenhouse produced by a high pressure oxygen rich atmosphere, until some cataclysm ended all but a present residual biosphere.